The red hand of fury : a Silas Quinn mystery - Morris, Roger, 1960- (Morris, Roger, 1960- Silas Quinn mystery., 2018)
A series of bizarre suicides leads Detective Inspector Silas Quinn to revisit his own troubled past ... June, 1914. A young man is mauled to death by a polar bear at London Zoo. Shortly afterwards, another young man leaps to his death from a notorious Suicide Bridge. Two seemingly unconnected deaths - and yet there are similarities. Following a third attempted suicide, DI Silas Quinn knows he must uncover the link between the three men if he is to discover what caused them to take their own lives. The one tangible piece of evidence is a card found in each of the victims' possession, depicting a crudely-drawn red hand. What does it signify? To find the answers, Quinn must revisit his own dark past. But can he keep his sanity in the process?